2009
DOI: 10.1111/j.1582-4934.2008.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells are resistant to TRAIL receptor‐mediated apoptosis

Abstract: New therapeutic approaches aim to eradicate tumours by expression of tumouricidal proteins in the tumour stroma. One such anti-neoplastic protein is tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) because it induces apoptosis in cancerous cells, but not in non-transformed cells. Stem cells can migrate to, survive and proliferate in tumours. We examined the suitability of bone marrow-derived adult mesenchymal stem cells (bmMSC), foetal-MSC and umbilical cord matrix stem cells (Wharton’s Jelly M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 16 publications
6
22
0
Order By: Relevance
“…Decreased MSC viability was unlikely to be caused by high levels of secreted TRAIL, as the extent of decrease in cell survival was comparable between MSC/ tTRAIL and MSC/dTRAIL despite the difference in their TRAIL induction. This result is supported by a previous observation that MSCs are resistant to TRAIL-mediated apoptosis (25). On the basis of these results, 50 MOI of rAd in the presence of Fe 3þ was determined to be the optimal condition for MSC transduction, which did not affect the phenotype of MSCs (Supplementary Fig.…”
Section: Dodecameric Form Of Trail Induces Higher Levels Of Tumor Celsupporting
confidence: 73%
“…Decreased MSC viability was unlikely to be caused by high levels of secreted TRAIL, as the extent of decrease in cell survival was comparable between MSC/ tTRAIL and MSC/dTRAIL despite the difference in their TRAIL induction. This result is supported by a previous observation that MSCs are resistant to TRAIL-mediated apoptosis (25). On the basis of these results, 50 MOI of rAd in the presence of Fe 3þ was determined to be the optimal condition for MSC transduction, which did not affect the phenotype of MSCs (Supplementary Fig.…”
Section: Dodecameric Form Of Trail Induces Higher Levels Of Tumor Celsupporting
confidence: 73%
“…It has already been shown that human embryonic stem cells (ESCs) (34,35), rat ESC-like cells (36), or MSCs (20) are more resistant to cell-mediated lysis and immune rejection than adult cells. The enhanced resistance of LSCs to cell-mediated lysis might be due to the presence of the FasL molecule on LSCs or to the resistance of SCs to TRAIL receptor-mediated apoptosis (36,37). Because it has been demonstrated that FasL can protect rat ESCs from rejection in an allogeneic host (38), we measured the level of FasL mRNA in the LSC fraction and in other limbal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to caspase-dependent apoptosis, under certain circumstances, death receptors can trigger a specific receptor-interacting protein (RIP)1/RIP3-dependent form of programmed necrosis called necroptosis [27,28]. Importantly, normal mesenchymal stem cells, progenitor cells, and terminally differentiated cells are resistant to death receptor-induced pro-death signaling [29][30][31]. In these cells, ligand-activated receptors may induce a number of other signaling events, for example, activation of the canonical NFkB pathway, mitogen-activated protein (MAP) and stress kinases, and the P3K/Akt axis, and can even enhance macroautophagy [32][33][34].…”
mentioning
confidence: 99%